Reduction of Formaldehyde Emission from Phenol Formaldehyde Treated Oil Palm Wood through Improvement of Resin Curing State - Mohamad Amarullah; Edi S. Bakar; Zaidon Ashaari; Mohd. H. Sahri; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2010)
Oil palm wood (OPW) has several imperfections, and impregnation with low molecular- weight phenol formaldehyde resin through a modified compreg method can practically enhance these properties. The treated OPW, however, releases a considerable amount of free formaldehyde and thus is unhealthy for the human being. To make it applicable for indoor material, formaldehyde emission (FE) should be lowered to 0.1 ppm or lower. The FE level of the treated OPW was reduced from 0.3 to 0.1 ppm or lower by improving the resin curing state through two approaches, i.e. modifying the hot pressing compression schedule during the process and adopting an extended drying after the process. It is acknowledged that the extended drying gave more effect on the FE reduction than that of modifying hot-pressing schedule. The combination pressing schedule of 12.5%®25%®50% and extended drying of 48 h emits the lowest, safe formaldehyde of 0.08-0.10 ppm, which is considered safe according to American National Standard Institute (ANSI) standard. The improving resin curing state through modifying the hot pressing schedule and adopting extended drying could be used as a practical way to reduce the FE level of the treated OPW to a safe level suitable for various furniture and indoor applications.